2016
DOI: 10.1038/srep24461
|View full text |Cite
|
Sign up to set email alerts
|

Hemoglobin consumption by P. falciparum in individual erythrocytes imaged via quantitative phase spectroscopy

Abstract: Plasmodium falciparum infection causes structural and biochemical changes in red blood cells (RBCs). To quantify these changes, we apply a novel optical technique, quantitative phase spectroscopy (QPS) to characterize individual red blood cells (RBCs) during the intraerythrocytic life cycle of P. falciparum. QPS captures hyperspectral holograms of individual RBCs to measure spectroscopic changes across the visible wavelength range (475–700 nm), providing complex information, i.e. amplitude and phase, about the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 30 publications
(55 reference statements)
1
33
0
Order By: Relevance
“…A diffraction phase microscope with a fluorescent arm capable of acquiring multiple fluorescent bands, as well as FRET signals, was constructed . The new QPI instrument employed a spectrally selected illumination of 670 nm with a bandwidth of 1.2 nm using a coherent white light source . Instead of using a typical off‐axis style interferometer arrangement, a diffraction phase interferometer was implemented.…”
Section: Methodsmentioning
confidence: 99%
“…A diffraction phase microscope with a fluorescent arm capable of acquiring multiple fluorescent bands, as well as FRET signals, was constructed . The new QPI instrument employed a spectrally selected illumination of 670 nm with a bandwidth of 1.2 nm using a coherent white light source . Instead of using a typical off‐axis style interferometer arrangement, a diffraction phase interferometer was implemented.…”
Section: Methodsmentioning
confidence: 99%
“…A detailed discussion about this correction is presented in Ref. . In this equation, the RI of the interstitial space of the natural tissue ( n 0 ( t = 0)) represents the RI of water according to our model.…”
Section: Methodsmentioning
confidence: 99%
“…The practical issue is whether there are detectable differences in values of α between RBCs from healthy controls and ones from diabetic patients. Related to this issue, it has been recently reported that the dramatic alterations in protein compositions and growing parasites at the late stage of malarial infection result in a significant discordance between the cytoplasmic oxy-Hb content and the phase-originated cellular drymass 68 .…”
Section: Common-path Diffraction Optical Tomography (Cdot) For Simulmentioning
confidence: 99%